A Markov decision process framework for optimal operation of monitored multi-state systems. (December 2018) - Compare, Michele; Marelli, Paolo; Baraldi, Piero; Zio, Enrico
We develop a decision support framework based on Markov decision processes to maximize the profit from the operation of a multi-state system. This framework enables a comprehensive management of the multi-state system, which considers the maintenance decisions together with those on the multi-state system operation setting, that is, its loading condition and configuration. The decisions are informed by a condition monitoring system, which estimates the health state of the multi-state system components. The approach is shown with reference to a mechanical system made up of components affected by fatigue.